2021
DOI: 10.3389/fmolb.2020.627774
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas13-Mediated Knockdown of lncRNA-GACAT3 Inhibited Cell Proliferation and Motility, and Induced Apoptosis by Increasing p21, Bax, and E-Cadherin Expression in Bladder Cancer

Abstract: The current study is to investigate the expression pattern and biological function of long non-coding RNA Focally gastric cancer-associated transcript3 (GACAT3) in bladder cancer. Real-time quantitative qPCR was used to detect the expression level of GACAT-3 in tumor tissues and paired normal tissues. Human bladder cancer T24 and 5637 cell lines were transiently transfected with specific CRISPR-Cas13 or negative control CRISPR-Cas13. Cell migration, proliferation, and apoptosis were measured by using wound hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In CRISPR-Cas13-transfected bladder cancer T24 and 5637 cell lines, GACAT3 promotes cell proliferation, suppresses apoptosis, and enhances cell migration by downregulating p21, BAX, and E-Cadherin protein levels, respectively. Mechanistically, GACAT3 acts as a ceRNA by interacting with miRNA-497 in the cytoplasm ( Zhang et al, 2020a ). These observations indicate that GACAT3 -targeted therapy is a promising strategy for bladder cancer.…”
Section: Expression Of Gacat3 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In CRISPR-Cas13-transfected bladder cancer T24 and 5637 cell lines, GACAT3 promotes cell proliferation, suppresses apoptosis, and enhances cell migration by downregulating p21, BAX, and E-Cadherin protein levels, respectively. Mechanistically, GACAT3 acts as a ceRNA by interacting with miRNA-497 in the cytoplasm ( Zhang et al, 2020a ). These observations indicate that GACAT3 -targeted therapy is a promising strategy for bladder cancer.…”
Section: Expression Of Gacat3 In Cancermentioning
confidence: 99%
“…A recent breakthrough in cancer research has been the discovery and application of lncRNA in comprehensive tumor therapy ( Bhan et al, 2017 ; Peng et al, 2017 ; Wang et al, 2019b ). An abundance of evidence has demonstrated that GACAT3 is a novel oncogenic lncRNA that functions as a ceRNA to modulate the occurrence and development of various tumors ( Feng et al, 2018 ; Zhong et al, 2018 ; Zhang et al, 2020a ).…”
Section: Future Clinical Applicationsmentioning
confidence: 99%
“…Recent progress in genome-editing techniques, such as CRISPR-based methods including CRISPR-interference (CRISPRi) and CRISPR-activation (CRISPRa), has brought the exciting possibility of transcriptionally silence or activate lncRNA expressing loci, and clearly demonstrate that these tools will be crucial for a better understanding of lncRNA biology ( Jinek et al, 2012 ; Cong et al, 2013 ; Mali et al, 2013 ; Qi et al, 2013 ; Gilbert et al, 2014 ; Thakore et al, 2015 ; Zhu et al, 2016 ; Abudayyeh et al, 2017 ; Liu S. J. et al, 2017 ; Chen et al, 2019 ; Phelan and Staudt, 2020 ; Wolter et al, 2020 ; Xu D. et al, 2020 ; Zhang et al, 2021 ). One way to achieve such transcriptional modulation is to use a dead-Cas9 approach.…”
Section: Targeting Lncrnas In Neurological Disorders: Trash or Treasure?mentioning
confidence: 99%
“…Significant attention has been directed toward applying CRISPR-Cas13 (RNA-targeting) technology as a diagnostic in the detection of low-frequency cancer somatic mutations 144 and in RNA editing. 85 , 145 Additionally, the CRISPR-Cas13 system has demonstrated highly efficient and specific knockdown of oncogenic mutant drivers, 146 gene fusions, 88 and ncRNA 147 transcripts in vitro with minimal off-targets, highlighting its potential for use as an RNA-based therapeutic tool. More recently, the potential of Cas13-based gene suppression in cancer immunotherapy has drawn attention due to its growing success in pre-clinical studies, as explored below.…”
Section: The Crispr-cas13 System Is a Novel Gene Interference Tool In Cancer Immunotherapymentioning
confidence: 99%